Jonathan Littell's Les Bienveillantes: Ethics, Aesthetics and the Subject of Judgment - Hutton, Margaret-Anne (Modern & contemporary France, 2010)
The article focuses on Jonathan Littell's Les Bienveillantes (2006) which it regards as part of an emerging cluster of French- and German-language 'Nazi perpetrator fictions' published from the mid-1990s onwards. The relationship between ethics and aesthetics, and the links of each to judgment, are explored via discussion of aspects of the reception of Littell's text, specifically, that it is kitsch and pro-Nazi. The status of the first-person narrator as an occupant of different subject positions (actor, self-conscious spectator, author) and the intertextual function of Hannah Arendt's Eichmann in Jerusalem and Kant's 'categorical imperative' are considered. A final section assesses the reader-both the narrator's fictional reader or addressee and Littell's 'real' reader-in the light of Arendt's later work on 'thinking' and judgment. L'article porte sur Les Bienveillantes (2006) de Jonathan Littell, ouvrage que nous considérons comme appartenant à un groupement de textes de langues française et allemande qui représentent des bourreaux nazis; groupement de textes dont il est possible d'observer l'émergence depuis le milieu des années 90. Le rapport entre éthique et esthétique, ainsi que les liens qu'ont les deux au jugement, sont analysés à la lumière de certains aspects de la réception du texte de Littell, en particulier, l'affirmation selon laquelle ce texte donne dans le kitsch et le pro-nazisme. Le statut du narrateur à la première personne en tant que sujet complexe (acteur, spectateur bien conscient de soi, auteur) et la fonction intertextuelle de l'Eichmann à Jérusalem de Hannah Arendt et de 'l'impératif catégorique' kantien sont évoqués. Une dernière section évalue le lecteur - à la fois lecteur ou destinataire fictif du narrateur et le lecteur 'réel' de Littell - à la lumière de l'oeuvre ultérieure d'Arendt sur la pensée et le jugement.